2020
DOI: 10.1080/10408363.2020.1774736
|View full text |Cite
|
Sign up to set email alerts
|

A summary of the diagnostic and prognostic value of hemocytometry markers in COVID-19 patients

Abstract: Many studies have reported hemocytometric changes in COVID-19 infection at admission and during the course of disease, but an overview is lacking. We provide a summary of the literature of hemocytometric changes and evaluate whether these changes may assist clinicians in diagnosing and predicting disease progression of COVID-19. Eighty-three out of 250 articles from December 2019 to 20 May 2020 were included from the databases, PubMed, Web of Science Core Collection, Embase, Cochrane and MedRxiv. Our review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
69
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 78 publications
11
69
0
1
Order By: Relevance
“…The observed differences are in line with data shown in previous studies [1][2][3][4][5]. These studies also reported that an increase in CK, LDH, CRP, AST and creatinine, together with a decreased number of lymphocytes, platelets and albumin levels are associated with a severe or fatal prognosis [1][2][3][4][5].…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The observed differences are in line with data shown in previous studies [1][2][3][4][5]. These studies also reported that an increase in CK, LDH, CRP, AST and creatinine, together with a decreased number of lymphocytes, platelets and albumin levels are associated with a severe or fatal prognosis [1][2][3][4][5].…”
supporting
confidence: 91%
“…Increased white blood cell (WBC) count seems to be a consistent finding in severely ill patients [2,4,5]. In contrast, our data shows no significantly increased WBC counts in the non-survivor group on admission, whereas the differences between neutrophils, lymphocytes and platelets in both groups are similar as previously described [1][2][3][4][5]. Similarly, there are no differences in alanine aminotransferase (ALT) or bilirubin values between the two groups, although this has been described by others [1,2,5].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Most studies were however geographically limited, had high risk for bias, and had no validation cohort (14). C-reactive protein, ferritin, Ddimer, albumin, urea nitrogen, bilirubin and lactate dehydrogenase (LDH) levels are cited as indirect indicators of the presence and severity of COVID-19 (11,13,(15)(16)(17)(18)(19)(20), as are complete blood count (CBC) and differential count (DIFF) changes, specifically lymphopenia, neutrophilia, high neutrophil-to-lymphocyte ratio (NLR) and thrombocytopenia (15,(21)(22)(23)(24)(25). All aforementioned parameters are widely available, but their value is constrained by significant inter-patient variability and limited specificity.…”
Section: Introductionmentioning
confidence: 99%